Phytochemistry-guided green synthesis of antimicrobial silver nanoparticles from cannabis sativa chemovars - Silva Sofrás, Fresia Melina (2026)
The phytochemical variability in Cannabis sativa L. chemovars represents an underexplored factor in environmentally sustainable nanomaterial production. In this study, three distinct chemovars, (i) High-Δ9-Tetrahydrocannabinol (THC) (89% THC), (ii) Balanced (60% Cannabidiol (CBD)), and (iii) High-CBD (89% CBD), were comparatively evaluated to determine their suitability for the green synthesis of silver nanoparticles (AgNPs). Ethanolic inflorescence extracts were used to recover bioactive secondary metabolites; among them, the High-CBD extract exhibited the highest total phenolic (3.34 mg gallic acid equivalent/g) and flavonoid (29.49 mg quercetine equivalent/g) contents, together with superior antioxidant capacity (53.16% 2,2-diphenyl-1-picrylhydrazyl free radical (DPPH) inhibition), indicating enhanced redox potential for nanoparticle formation. The terpene profile of High-CBD showed a dominance of myrcene (21.4%), contributing to the stabilization of the system. Using the High-CBD extract, predominantly spherical nanoparticles of 5 ± 0.9 nm were synthesized and confirmed by UV–vis, EDS, and TEM. The biogenic AgNPs demonstrated significant dose-dependent antibacterial activity, with minimum bactericidal concentration (MBC) of 1.0 mg/mL against Staphylococcus aureus and 4.5 mg/mL against Escherichia coli. These findings highlight the critical role of chemovar-dependent phytochemical composition and support a phytochemistry-guided approach for developing silver nanoparticles with potential biomedical applications.